A critical evaluation on efficacy of recrystallization vs. strain induced boundary migration in achieving grain boundary engineered microstructure in a Ni-base superalloy. (March 2018) - Prithiv, T.S.; Bhuyan, P.; Pradhan, S.K.; Subramanya Sarma, V.; Mandal, S.
Abstract: A critical evaluation of recrystallization vs. strain induced boundary migration (SIBM) as the mechanism responsible behind the grain boundary engineering (GBE) in alloy 617 is made. Towards this hot deformation processing (in the temperature range of 1173–1473 K and strain rates of 0.001–10 s −1 ) as well as GBE-type iterative processing is performed on solution-annealed specimen. GBE-quantifying parameters such as Σ3 n fraction, triple junction distribution, twin-related grain size ratio, twin-related domain (TRD) parameters and fractal dimension have been utilized to quantify the extent of GBE in the processed microstructures. Occurrence of dynamic recrystallization (DRX) during hot deformation processing does not induce notable multiple twinning leading to a microstructure analogous to that of solution-annealed condition even after complete DRX. Following GBE-type iterative processing, GBE microstructure has only been achieved when prolific multiple twinning occurred due to activation of SIBM leading to a high fraction of Σ3 n boundaries (∼79%) with most of the twins being part of the grain boundary network. Consequently, an increasing proportion of J2 and J3 triple junctions with a concomitant increase in both the average number of grains per TRD and twin-related grain size ratio are achieved. However, occurrence of static recrystallization during GBE-type processing has led to smaller TRD size and copious random boundaries connectivity as confirmed by fractal analysis thus clearly suggesting that SIBM, not recrystallization catalyzes the profusion of Σ3 n boundaries. As GBE relies on the multiple twinning mechanisms promoted via SIBM, recrystallization needs to be circumvented for successful attainment of GBE microstructure. Graphical abstract: Image 1